Decomposition and phase transformation mechanisms of α2 lamellae in β-solidified γ-TiAl alloys. (1st January 2023) - Liu, Yan; Li, Jinshan; Tang, Bin; Song, Lin; Wang, William Yi; Liu, Dong; Yang, Rui; Kou, Hongchao
Abstract: The decomposition of (α2 /γ) lamellae during service is an important microstructure degradation phenomenon that is worth studying. In this study, the decomposition mechanism of (α2 /γ) lamellae was systematically investigated by transmission electron microscopy (TEM) and high-angle annular dark-field scanning transmission electron microscopy (HAADF-STEM) techniques. The results showed facilitated α2 →βo phase transformation by [11 2 ¯ 0]α2 /[0 1 ¯ 1]γ semi-coherent α2 /γ interface due to its larger misfit than that of [11 2 ¯ 0]α2 /[ 1 ¯ 10]γ interface. Ellipsoidal ωo particles were formed at βo /α2 interface and nucleated at the interface dislocations. The energy-dispersive X-ray spectroscopy (EDS) results demonstrated feasible depletion of Mo and enrichment of Ti at α2 /βo interface to form ωo phase. In addition, lath-shaped ωo precipitates were observed between two precipitated large βo grains formed by direct α2 →ωo phase transformation. The formation mechanism of the lath ωo phase was attributed to both element segregation and strain accommodation caused by βo precipitate in α2 lamellae. The α2 /βo interface served as preferential nucleation sites for ωo phase due to the atomic structure of the interface, which crystallographically was closely associated with the structure of ωo phase. Moreover, βo precipitates at low stress introduced stacking faults in α2 lamellae, while delaying the parallel decomposition of α2 lamellae at high stress. In sum, these findings provided profound insights into the decomposition mechanism of (α2 /γ) lamellae, relevant as theoretical basis for controlling the microstructures and improving the performance of β-solidified γ-TiAl alloys. Graphical abstract: Image, graphical abstract